PENGEMBANGAN KOMIK IPA BERBASIS KEARIFAN LOKAL TERINTEGRASI HOTS KELAS V MATERI ORGAN GERAK PADA HEWAN DAN MANUSIA - Gilang Setia Mahendra; Sugeng Eko Putro Widoyoko; Nur Ngazizah (Jurnal Bionatural, 2024)
Teaching materials generally consist of knowledge, skills and actions that must be carried out by students in order to achieve the expected competencies. Comics are an example of teaching material. The current generation is less interested in preserving its local wisdom. Research Objectives: 1) Produce a science comic product based on integrated local wisdom HOTS class V Material on Movement Organs in Animals and Humans. 2) Knowing the feasibility of Class V HOTS Local Wisdom Based Science comics on Animal and Human Movement Organs. The method used in this research is R&D and uses the 4D (Four D) model, namely Define, Design, Develop and Disseminate. The results of this development research 1) Have produced a product in the form of "Science Comics on Animal and Human Movement Organ Material Based on Integrated Local Wisdom HOTS". 2) The feasibility results from media experts obtained a score of 36 with a mean of 3.6, material experts obtained a score of 50 with a mean of 3.80, the educator's assessment obtained a score of 88 with a mean of 3.8 which was categorized as feasible. Practicality through limited testing of student responses with a score of 173 with an average of 3.6 and broad 393 with an average of 3.6 and the implementation of limited and broad learning received a score of 11 with an average of 3.6 and was categorized as practical. The results from experts and trials state that the product can be used in the learning process.